2013
DOI: 10.1016/j.bbamem.2013.04.020
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal AH2 segment of protein NS4B from hepatitis C virus. Binding to and interaction with model biomembranes

Abstract: HCV NS4B, a highly hydrophobic protein involved in the alteration of the intracellular host membranes forming the replication complex, plays a critical role in the HCV life cycle. NS4B is a multifunctional membrane protein that possesses different regions where diverse and significant functions are located. One of these important regions is the AH2 segment, which besides being highly conserved has been shown to play a significant role in NS4B functioning. We have carried out an in-depth biophysical study aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 68 publications
3
11
0
Order By: Relevance
“…Furthermore, as pointed out above, the shallow penetration of some AHs leads to the generation of local membrane curvature through the pushing of the lipid headgroups apart (the "wedge" mechanism) (McMahon and Gallop, 2005;Campelo et al, 2008;Drin and Antonny, 2010;Baumgart et al, 2011;Lai et al, 2012;McMahon and Boucrot, 2015; and references therein). At least in some cases, the depth of the AH insertion into the membrane depends on the presence of negatively charged lipids in the membrane (Sani et al, 2012;Palomares-Jerez et al, 2013). Indeed, the interaction of curvature-inducing AHs with anionic lipids might contribute to the optimal depth of AH insertion.…”
Section: Topology Of Fissionmentioning
confidence: 99%
“…Furthermore, as pointed out above, the shallow penetration of some AHs leads to the generation of local membrane curvature through the pushing of the lipid headgroups apart (the "wedge" mechanism) (McMahon and Gallop, 2005;Campelo et al, 2008;Drin and Antonny, 2010;Baumgart et al, 2011;Lai et al, 2012;McMahon and Boucrot, 2015; and references therein). At least in some cases, the depth of the AH insertion into the membrane depends on the presence of negatively charged lipids in the membrane (Sani et al, 2012;Palomares-Jerez et al, 2013). Indeed, the interaction of curvature-inducing AHs with anionic lipids might contribute to the optimal depth of AH insertion.…”
Section: Topology Of Fissionmentioning
confidence: 99%
“…Although the structure of NS4B has yet to be determined, NMR studies of AH2 have revealed that the peptide adopts a monomeric α-helical conformation in detergent micelles [15] . Fluorescence-quenching studies have shown that upon reconstitution into lipid bilayers, the amphipathic helix lies at a shallow location close to the bilayer surface, consistent with at least one of its proposed topologies [22] . Whilst these properties appear to be largely invariant with respect to the lipid bilayer compositions studied to date, the effect of the AH2 domain on lipid bilayers and its potential role in membrane remodelling remains unclear.…”
Section: Introductionmentioning
confidence: 66%
“…Mutations in AH2 that disrupt both these two features block viral replication and affect the appearance of the membranous web/NS protein foci in cells. A final feature of AH2 important for its role in membrane remodelling is that it exhibits specific interactions with lipids present in the bilayer including a range of anionic phosphatidylinositol phosphates [22] , lipids whose levels within the bilayer are important for the replication of HCV and many other positive strand RNA viruses [23] , [24] . Recruitment/retainment of phosphatidylinositol phosphates and other lipids within the membranous web by NS4B could help modulate bilayer malleability and alter local curvature.…”
Section: Introductionmentioning
confidence: 99%
“…4). The five blocks from positions 68 to 193 roughly correspond to five transmembrane domains that have been proposed (33). This enabled us to look sequentially and rapidly across NS4B at the amino acid differences between genotypes 1b and 2a that may have contributed to the observed potency differences.…”
Section: Resultsmentioning
confidence: 99%
“…AH2 extends from amino acids 42 to 66 and has the ability to traverse the lipid bilayer following oligomerization (30). The central region of NS4B comprises several transmembrane (TM) domains which are involved in membrane anchoring and ER retention (32)(33)(34). The precise limits of each TM region have not been determined, but they are postulated to consist of a series of approximately 20-amino-acid stretches following the Nterminal AH2 (34).…”
mentioning
confidence: 99%